Taxonomy of Existing Sustainable Smart City IoT Projects - Frederick T. Sheldon; Youssef Saleh; Matthew Cox; Ananth A. Jillepalli; Bhaskar P. Rimal; Ahmed Abdel-Rahim (IEEE Access)
There has been a significant increase in the inclusion of the Internet of Things (IoT) into systems that affect everyone daily. The lessons learned from past experiences (i.e., case studies) can give a clearer understanding of the various options useful for potential improvements. Moreover, given the diversity of projects across privately funded versus government-funded, we took an independent, objective and scientific approach to understanding the differences comparatively. Starting with the funding sources and feature rationale, a clearer picture has emerged. Consequently, the composite picture enables a different, perhaps more valuable, baseline from which to develop future smart city strategies. Moreover, there can be many positives and negatives to the way these projects were implemented and carried out (i.e., commercial and political stakes). This study was limited from the post-implementation perspective, which emphasizes success stories, an inherent bias, as well as a disparity in level-of-funding available for each of the projects. Nevertheless, we have provided an original and consolidated perspective of the project outcomes and results. This represents a useful opportunity to explore an array of Smart City implementations that depend on evolving IoT technology solutions. Unfortunately, not all solutions being employed today are interoperable and/or extensible in an open systems sense. Modification, extensions, and support toward addressing emerging needs and achieving better more sustainable community mobility therefore may be disadvantaged and/or impeded; Thus, to better manage the expectations of Smart City planners and developers, this article has assessed and organized the outcomes of the eight projects posthumously and comparatively.